Contemporary Native American literature - Tillett, Rebecca (BAAS paperbacks., 2007)
"This introduction to contemporary Native American literature is suitable for students with little or no knowledge of the subject, or of Native American culture or history." "It examines influential texts in the context of the historical moment of their production, with reference to significant literary developments. Most importantly, Native literature is assessed within the wider socio-political context of American colonialism, the history of Federal-Indian relations and policies, popular perceptions of 'Indians', and contemporary Native economic, social, and political realities."--Jacket